2012
DOI: 10.1371/journal.pgen.1002725
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Activated Cdc42 Kinase Has an Anti-Apoptotic Function

Abstract: Activated Cdc42 kinases (Acks) are evolutionarily conserved non-receptor tyrosine kinases. Activating somatic mutations and increased ACK1 protein levels have been found in many types of human cancers and correlate with a poor prognosis. ACK1 is activated by epidermal growth factor (EGF) receptor signaling and functions to regulate EGF receptor turnover. ACK1 has additionally been found to propagate downstream signals through the phosphorylation of cancer relevant substrates. Using Drosophila as a model organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…As depletion of hpo kinase results in the hyperactivation of Yki, we hypothesized that the abrogated eye development observed in ey4hpo-RNAi or ey4wts-RNAi flies grown on caffeine was a consequence of increased Yki activity. As previously reported, 49 eye-specific overexpression of yki causes overgrowth of eye tissue (Figure 4d). When flies of the same genotype were reared on caffeine food, they displayed abnormally round eyes, which were also rough and appeared to contain less pigment, suggesting that caffeine exposure reduced the eye overgrowth phenotype because of increased apoptosis (Figure 4d).…”
Section: Resultssupporting
confidence: 88%
“…As depletion of hpo kinase results in the hyperactivation of Yki, we hypothesized that the abrogated eye development observed in ey4hpo-RNAi or ey4wts-RNAi flies grown on caffeine was a consequence of increased Yki activity. As previously reported, 49 eye-specific overexpression of yki causes overgrowth of eye tissue (Figure 4d). When flies of the same genotype were reared on caffeine food, they displayed abnormally round eyes, which were also rough and appeared to contain less pigment, suggesting that caffeine exposure reduced the eye overgrowth phenotype because of increased apoptosis (Figure 4d).…”
Section: Resultssupporting
confidence: 88%
“…While Hsp26 has no effect on fl y survival to hid-, reaper-and grim-induced lethality when over-expressed in neurons (Liao et al 2008 ), it was shown to interact with activated Cdc42 kinase (ack) together with Hsp23 and some other proteins in an affi nity assay on S2 cells (Schoenherr et al 2012 ). Ack is an anti-apoptotic protein, which blocks programmed cell death induced by hid and reaper.…”
Section: Shsps and Apoptosismentioning
confidence: 99%
“…Ack is an anti-apoptotic protein, which blocks programmed cell death induced by hid and reaper. While the knockdown of Hsp23 had no effect on ack anti-apoptotic activity, the knockdown of Hsp26 was shown to suppress this activity (Schoenherr et al 2012 ). These results demonstrate the distinctive features of Drosophila sHsps and suggest that Hsp26 functions directly with ack or in a parallel pathway to regulate survival.…”
Section: Shsps and Apoptosismentioning
confidence: 99%
“…Most mammalian cells undergo cell cycle arrest followed by apoptosis when ACK1 protein is depleted by silencing RNA, or when treated with ACK1-specific small molecule inhibitors [19; 20; 35]. The pro-proliferative function of ACK1 like proteins is conserved in the fruit fly, Drosophila [36]. Drosophila Ack resembles human TNK1 in domain organization, but retains significant sequence identity/similarity with ACK1/TNK2 in all conserved domains including the activation loop [36].…”
Section: Introductionmentioning
confidence: 99%
“…The pro-proliferative function of ACK1 like proteins is conserved in the fruit fly, Drosophila [36]. Drosophila Ack resembles human TNK1 in domain organization, but retains significant sequence identity/similarity with ACK1/TNK2 in all conserved domains including the activation loop [36]. While homozygous female flies with Ack 86 null alleles are normal, the males are sterile.…”
Section: Introductionmentioning
confidence: 99%